(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
This article provides a detailed analysis of the morphological and functional properties of human muscle tissue, their structural levels and biochemical basis. Muscle tissue - smooth, cardiac and skeletal muscles - each has its own unique structure and function, and their cellular and tissue-level structures and physiological processes carried out through them are studied. Also, the energy sources of muscles, metabolic pathways (anaerobic and aerobic), ATP synthesis, creatine phosphate system and glycogenesis processes are considered from a biochemical point of view. The article covers the movement of muscle tissue in the human body, the biochemistry of the muscle contraction mechanism, clinical conditions and biochemical changes.